Morphology of the first larval stage of Macrobrachium brasiliense (Heller, 1868) (Caridea: Palaemonidae) - Pantaleão, João Alberto Farinelli [UNESP]; Gregati, Rafael Augusto [UNESP]; Taddei, Fabiano Gazzi; Costa, Rogério Caetano da [UNESP] (Sociedade Brasileira de Carcinologia, 2011)
In this paper, we describe and illustrate the morphology of the first larval stage of the prawn Macrobrachium brasiliense. Two ovigerous females were obtained in a stream environment, which belongs to Paraná River Basin, Southeastern of Brazil, and were maintained in laboratory until the time of hatching. The newly-hatched larva bears very advance morphological features, with benthic habits. They had sessile eyes and all appendages, except for the uropods; however, most of the appendages were not fully formed. The description given here is compared with the first larval stage of Macrobrachium species with abbreviated larval development from other localities.
Keywords: Palaemonoidea; Larval development; First zoea; Abbreviated development; Larval morphology